Assessing the chemical profile and biological potentials of Tamarix smyrnensis flower extracts using different solvents by in vitro, in silico, and network methodologies - Erdi Can Aytar; Emine Incilay Torunoğlu; Abidin Gümrükçüoğlu; Saleh Al-Farraj; Alper Durmaz; Mika Sillanpää (PLoS ONE, 2025)
This study evaluated the antioxidant properties, phytochemical content, and protein interactions of Tamarix smyrnensis flower extracts prepared with different solvents (methanol, ethanol, ethyl acetate). The antioxidant activities were assessed using the DPPH, metal chelation, and CUPRAC assays. Ethanol extracts exhibited the strongest radical scavenging activity (IC 50 = 25.15 µg/mL), while methanol extracts showed superior metal chelation (49.84 mg/mL) and reducing power (IC 50 = 35.95 µg/mL). HPLC analysis identified key bioactive compounds, with p-coumaric acid, catechin, and gallic acid being the most abundant phenolics and flavonoids across the extracts. Methanol extracts were rich in 4-hydroxybenzoic acid (2253.9 mg/L) and catechin (6974.4 mg/L). Molecular interaction predictions using the STITCH database revealed that phenolic compounds such as 4-hydroxybenzoic acid, catechin, and p-coumaric acid have significant interactions with proteins involved in antioxidant defence, including COQ2 and HMOX1. STRING-based protein–protein interaction (PPI) analysis further highlighted a network of proteins involved in mitochondrial function and oxidative stress response, suggesting that T. smyrnensis phenolics could modulate these pathways. Molecular docking studies confirmed that chlorogenic acid and catechin showed strong binding affinities with the antioxidant-related protein PTGS2, indicating their potential as therapeutic agents. The findings emphasise the significant antioxidant potential of T. smyrnensis flower extracts, driven by their rich phytochemical content and promising bioactivity, offering a foundation for future therapeutic applications targeting oxidative stress-related diseases.